1975
DOI: 10.1021/bi00676a008
|View full text |Cite
|
Sign up to set email alerts
|

Bombyx mori silk proteins. Characterization of large polypeptides

Abstract: Proteins taken directly from the Bombyx mori silk gland have been separated and identified as either fibroin or sericin on the basis of their location within the gland and their amino acid composition. Molecular weights of these polypeptides have been determined by sodium dodecyl sulfate polyacrylamide gel electrophoresis, and by agarose-guanidine chromatography. Fibroin consists of approximately equimolar amounts of two large (350,000) polypeptide chains. These may be the products of distinct fibroin alleles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(68 citation statements)
references
References 28 publications
3
64
0
Order By: Relevance
“…Group 7 shows a segregation ratio of phenotypes in the F2 hybrid obtained by crossing the Fl hybrid of F x S. The ratio of F to FS and S was almost 1:2:1. Groups 8 and 9 show a segregation ratio of phenotype in the backcrosses of MS x M Sprague (1975) has demonstrated that fibroin can be electrophoretically resolved into two large polypeptide chains and suggested the possibility that this may be the products of distinct fibroin alleles present in hybrid silkworm strains. Recently, Sprague et al (1979) have presented evidence showing the existence of fibroin genes of different length.…”
Section: Crosses Of Parent Strains Of Silkwormmentioning
confidence: 99%
See 1 more Smart Citation
“…Group 7 shows a segregation ratio of phenotypes in the F2 hybrid obtained by crossing the Fl hybrid of F x S. The ratio of F to FS and S was almost 1:2:1. Groups 8 and 9 show a segregation ratio of phenotype in the backcrosses of MS x M Sprague (1975) has demonstrated that fibroin can be electrophoretically resolved into two large polypeptide chains and suggested the possibility that this may be the products of distinct fibroin alleles present in hybrid silkworm strains. Recently, Sprague et al (1979) have presented evidence showing the existence of fibroin genes of different length.…”
Section: Crosses Of Parent Strains Of Silkwormmentioning
confidence: 99%
“…Sasaki and Noda (1974) identified two amino acids (Asp and Ser) in a ratio of about 1:1 as the N-terminal amino acids of fibroin large subunit. Sprague (1975) demonstrated that fibroin was resolved into two bands on SDS-polyacrylamide gel electrophoresis and suggested the possibility that these two large polypeptides might be the products of fibroin alleles present in hybrid silkworm strains.…”
Section: Introductionmentioning
confidence: 99%
“…mori larvae were hatched from a laboratory stock of eggs, and were reared on an artificial diet as described previously. 12 Preparation of labelled 18S RNA Ribosomal RNA was labelled in vivo by feeding 32pO4 (carrier free, New England Nuclear) to larvae on the fifth day of the fifth instar. Each larva received 3-4 mCi of 32pO4 mixed with approximately 0.5 g of the diet, and was maintained subsequently on diet without added 32pO4.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…4) Gamo et al estimated the molecular masses of sericins to be 309, 177, 145, 80, and 134 kDa, 6) while Sprague reported at least 15 diŠerent sericins ranging from about 20 to 220 kDa in the anterior portion of the middle silk gland. 7) Recent studies on sericin genes provided further information about the constituents of sericin. The Ser1 gene was reported to produce mRNAs with sizes of 10.5, 9.0, 4.0, and 2.8 kb by alternative splicing, 8) and the Ser2 gene was found to produce mRNAs with sizes of 6.4 or 5.0 and 3.1 kb.…”
mentioning
confidence: 99%